Website Resource Monitoring Platform Supporting Tibetan and Uyghur Language based on Semantics - Lirong Qiu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
With the development of the Internet and the increasing minority language websites, people of ethnic minorities begin to browse the news, comments and other content on the Internet according to their own interests. At present, there is still no websites to provide the Chinese–Tibetan or Chinese-Uyghur co-occurrence search engine in China. In this paper, a platform for Tibetan and Uyghur website monitoring is proposed. The functions and characterizes are proposed in detail. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3137